Pemanfaatan Digital Marketing Untuk Optimalisasi Pemasaran Produk UMKM Di Masa Pandemi Covid-19 (Desa Gesang Kecamatan Tempeh Kabupaten Lumajang) - Dita Indah Puspitasari; Hadziqul Abror (Puslitbang Sinergis Asa Professional, 2022)
Marketing is one of the activities to maintain the continuity of a business, aiming to develop the business that is run and obtain a profit from the sales. Online media marketing or commonly called digital marketing can be said as a solution for running a promising business today, especially during the covid 19 pandemic. This service activity was carried out for MSME cake production in Gesang village- Lumajang with the theme